OPTIMAL LOGISTIC AND ENERGY MANAGEMENT OF ELECTRIC VEHICLE CHARGING PROCESSES IN DISTRIBUTION ELECTRIC NETWORKS - Kuchkarbekovich, Tagaev Baxodir; qizi, Qo‘chqorbekova Nigora Baxtiyor; Baxtiyorovna, Quchqorbekova Dilnoza (Research Focus International Scientific Journal, 2026)
This article examines the issues of efficient organization of electric vehicle charging processes in distribution electric networks. Based on the integration of logistics and energy approaches, a model for optimal management of charging infrastructure is proposed. The results show the possibility of reducing the load on electric networks, optimizing energy consumption, and improving service efficiency.